PSVII-6 Effects of Carbohydrase Mixture Supplementation and Fiber Level on Apparent Total Tract Digestibility of Nutrients in Diets Fed to Gestating Sows. (12th April 2022) - Shipman, Garrin; Perez-Palencia, Jorge Y; Patterson, Rob; Levesque, Crystal L
Abstract: Supplementation of multi-carbohydrase enzyme cocktails increase nutrient digestibility of fibrous diets in grower pigs, in particular, dietary non-starch polysaccharides (NSP); while NSP degrading enzymes are extensively used in sow diets there is little data characterizing NSP enzyme effect in sow diets. The objective of this study was to evaluate the effect of carbohydrase mixture (CM) supplementation on apparent total tract digestibility (ATTD) of energy and nutrients in diets with low or high fiber content fed to pregnant sows. A total of 45 gestating sows (parity 0 to 5; BW 187 ± 28 kg) were blocked by parity in a 2 x 3 factorial arrangement to either a high (HF; 17.5% NDF) or low fiber (LF; 13% NDF) diet and 1 of 3 levels of CM supplementation (0, 0.08, and 0.10%). Sows were fed once daily at 2.2 kg/d. Fecal and urine samples were collected for 4 d following a 10-day adaption period. Dietary CM supplementation to gestating sow diets increased ATTD of dry matter, energy, crude fat, and fiber (NDF and ADF; P < 0.05) with tendencies ( P < 0.10) for crude fiber. Digestibility of calcium, phosphorus, NSPs along with ME and DE contents of the diets were not affected ( P > 0.05). Dietary CM supplementation to the LF diet, but not the HF diet, increased the ATTD of NDF ( P = 0.02). Inclusion at 0.08% did not differ from the 0.1% inclusion for effects on ATTD (Table 1). Irrespective of CM supplementation, sows fed the HF diet had improved digestibility of total NSP, xylose, glucose, and uronic acids ( P < 0.05) with a tendency for galactose ( P = 0.08) as well as increased DE and ME content ( P < 0.01). Inclusion of CM in high fibrous gestating sow diets can be utilized to increase ATTD of nutrients and energy.